Advanced Korean Industrial Safety and Health Policy with Risk Assessment - Hyuckmyun Kwon; Jae Hyun Cho; Il Moon; Jaewook Choi; Dooyong Park; Youngsoon Lee (Elsevier, 2010)
This article describes a systematic roadmap master plan for advanced industrial safety and health policy in Korea, with an emphasis on. Since Korean industries had first emergence of industrial safety and health policy in 1953, enormous efforts have been made on upgrading the relevant laws in order to reflect real situation of industrial work environment in accordance with rapid changes of Korean and global business over three decades. Nevertheless, current policy has major defects; too much techniques-based articles, diverged contents in less organization, combined enforcement and punishments and finally enforcing regulations full of commands and control. These deficiencies have make it difficult to accommodate changes of social, industrial and employment environment in customized fashion. The approach to the solution must be generic at the level of paradigm- shift rather than local modifications and enhancement. The basic idea is to establish a new system integrated with a risk assessment scheme, which encourages employers to apply to their work environment under comprehensive responsibility. The risk assessment scheme is designed to enable to inspect employers' compliances afterwards. A project comprises four yearly phases based on applying zones; initially designating and operating a specified risk zone, gradually expanding the special zones during a period of 3 years (2010-2012) and the final zone expanded to entire nation. In each phase, the intermediate version of the system is updated through a process of precise and unbiased validation in terms of its operability, feasibility and sustainability with building relevant infrastructures as needed.